Study on Electrical Conduction Properties of Plasticized CMC-DTAB Based Solid Biopolymer Electrolytes - Norfatihah, Mazuki; Singh, Pramod K.; Ahmad Salihin, Samsudin (Trans Tech Publications Ltd, Switzerland, 2021)
This work focuses on the electrical properties study of solid biopolymer electrolyte (SBE) based plasticized carboxy methylcellulose (CMC) doped dodecyltrimethyl ammonium bromide (DTAB). Different weight percentage of ethylene carbonate (EC) which acts as plasticizer was incorporated into SBE system and were successfully prepared via solution casting technique. The conduction properties of SBE was investigated by using electrical impedance spectroscopy (EIS). The incorporation of 10 wt.% EC was found to achieve the highest ionic conductivity with 1.00 × 10-3 S cm-1 at room temperature. All SBE samples shows the ionic conductivity increased proportionally with temperature thus obeys to Arrhenius behaviour with regression value almost close to unity (R2~1). The electrical conduction behaviour of the CMC-DTAB-EC SBE reveals non-Debye behaviour without single relaxation properties